Trends in Reoperation for Surgical Site Infection After Spinal Surgery With Instrumentation in a Multicenter Study. Issue 20 (15th October 2020) - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Nakashima, Hiroaki; Kato, Fumihiko; Sato, Koji; Kanemura, Tokumi; Matsubara, Yuji; Yoshihara, Hisatake; Hirasawa, Atsuhiko; Deguchi, Masao; Shinjo, Ryuichi; et al.
Abstract : Study Design: A multicenter retrospective analysis of a prospectively maintained database. Objective: To examine the characteristics of reoperation for surgical site infection (SSI) after spinal instrumentation surgery, including the efficacy of treatment for SSI and instrumentation retention. Summary of Background Data: Aging of the population and advances in surgical techniques have increased the demand for spinal surgery in elderly patients. Treatment of SSI after this surgery has the main goals of eliminating infection and retaining instrumentation. Methods: The subjects were 16, 707 patients who underwent spine surgery with instrumentation in 11 hospitals affiliated with the Nagoya Spine Group from 2004 to 2015. Details of those requiring reoperations for SSI were obtained from surgical records at each hospital. Results: There were significant increases in the mean age at the time of surgery (54.6–63.7 years) and the number of instrumentation surgeries (726–1977) from 2004 to 2015. The incidence of reoperation for SSI varied from 0.9% to 1.8%, with a decreasing trend over time. Reoperation for SSI was performed in 206 cases (115 men, 91 women; mean age 63.2 years). The average number of reoperations (1.4 vs. 2.3, P  < 0.05), time from SSI to first reoperation (4.3 vs. 9.5 days, P  < 0.05), and the methicillin-resistant Staphylococcus identification rate (20% vs. 37%, P  < 0.01) were all significantly lower in cases with instrumentation retention (n = 145) compared to those with instrumentation removal (n = 61). Conclusion: There were marked trends of aging of patients and an increase in operations over the study period; however, the incidences of reoperation and instrumentation removal due to SSI significantly decreased over the same period. Rapid debridement after SSI diagnosis may have contributed to instrumentation retention. These results can serve as a guide for developing strategies for SSI treatment and for improved planning of spine surgery in an aging society. Level of Evidence: 3